The Antibacterial Assay of Tectorigenin with Detergents or ATPase Inhibitors against Methicillin-Resistant Staphylococcus aureus - Dae-Ki Joung (Evidence-Based Complementary and Alternative Medicine, 2014)
Tectorigenin (TTR) is an O-methylated isoflavone derived from the rhizome of Belamacanda chinensis (L.) DC. It is known to perform a wide spectrum of biological activities such as antioxidant, anti-inflammatory, anti-tumor. The aim of this study is to examine the mechanism of antibacterial activity of TTR against methicillin-resistant Staphylococcus aureus (MRSA). The anti-MRSA activity of TTR was analyzed in combination assays with detergent, ATPase inhibitors, and peptidoglycan (PGN) derived from S. aureus. Transmission electron microscopy (TEM) was used to monitor survival characteristics and changes in S. aureus morphology. The MIC values of TTR against all the tested strains were 125 μg/mL. The OD(600) of each suspension treated with a combination of Triton X-100, DCCD, and NaN3 with TTR (1/10 × MIC) had been reduced from 68% to 80%, compared to the TTR alone. At a concentration of 125 μg/mL, PGN blocked antibacterial activity of TTR. This study indicates that anti-MRSA action of TTR is closely related to cytoplasmic membrane permeability and ABC transporter, and PGN at 125 μg/mL directly bind to and inhibit TTR at 62.5 μg/mL. These results can be important indication in study on antimicrobial activity mechanism against multidrug resistant strains.